Fabrication of the microchannels on PMMA using frequency doubled Nd:YAG laser. (12th December 2017) - Pazokian, Hedieh; Sobhani, Mohammad Javad; Mollabashi, Mahmoud; Amiri, Hosein
Abstract: In this paper, the second harmonic of Nd:YAG laser was used for the fabrication of microchannels (microholes) in polymethylmethacrylate. It was found that irradiation parameters as well as focusing lens focal length have significant effect on the geometry of the microchannels; while, the quality of the channels is dominantly affected by the focusing lens focal length. Our results also show that the maximum accessible depth is increased with sample movement in drilling direction at an appropriate velocity.